Analisis Strategi Pemasaran UMKM Di Era 4.0 - Mashuri Mashuri (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2019)
This research is literature research, aimed at knowing how to analyze the marketing strategies used by micro, small and medium businesses in the digital age 4.0. The results of the analysis in this study found that micro, small and medium enterprises in Indonesia are still low when compared to other countries. The contribution of the micro, small and medium business sector to national exports was 15.80% lower than Malaysia 19.00%, Sri Lanka 20.00%. One contributing factor to the low contribution rate is the lack of potential use of existing resources by micro, small and medium business actors such as the use of mobile social media. Through the digital era 4.0 the marketing system of the micro, small and medium business sector is expected to utilize the maximum potential so that it can grow inclusive and sustainably.